1999
DOI: 10.1007/bf02932268
|View full text |Cite
|
Sign up to set email alerts
|

A study of comparison between the nationwide epidemiological survey in 1991 and previous surveys on behçet’s disease in Japan

Abstract: The 4th nationwide epidemiological survey on Beh~et disease (BD), which included all patients with BD at 1,200 hospitals selected at random from 10,081 hospitals in Japan, was carried out by the BD Research Committee of the Ministry of Health and Welfare in 1991 to examine the epidemiological features of BD in Japan by comparing with previous surveys.3,938 patients from these hospitals were examined by the Japanese diagnostic criteria of BD (JCBD) revised in 1987 and the International criteria for dassiflcatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…2,5 Data from an epidemiologic BD survey in Japan showed that the number of patients with incomplete BD had increased between 1972 and 1991, while the number of patients with complete BD was sustained. 29 The increased ratio of incomplete/complete BD in the late 2000s compared to the 1990s was statistically significant in this study and may be associated with better visual prognosis. This result is in agreement with similar data from the Japanese epidemiologic survey.…”
Section: Discussionmentioning
confidence: 68%
“…2,5 Data from an epidemiologic BD survey in Japan showed that the number of patients with incomplete BD had increased between 1972 and 1991, while the number of patients with complete BD was sustained. 29 The increased ratio of incomplete/complete BD in the late 2000s compared to the 1990s was statistically significant in this study and may be associated with better visual prognosis. This result is in agreement with similar data from the Japanese epidemiologic survey.…”
Section: Discussionmentioning
confidence: 68%
“…However, considering the general low frequency of gastrointestinal involvement in BD (1.6% in Turkey, 12% in Germany, 10-15% in Japan) (2,17,18,20) and the lower fi-equency of eye lesions in this study, it was remarkable that 21.1 % of the patients (4 of 19 who had the EN-like lesions with vasculitis type) showed severe BD with gastrointestinal involvement. A multicentre study disclosed that, in patients with BD, male sex and a younger age at onset are associated with more severe disease (2).…”
Section: Discussionmentioning
confidence: 63%
“…The patients with these EN-type lesions were clinically characterized as being exclusively female, and to have mild cases of BD. Recent studies show that the clinical manifestations of BD tend to be milder than those previously reported in Japanese patients and the mild cases without eye lesions show a female predominance (17). The presence of the EN-type lesion may be an indicator of the mildness of BD.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations